Telaah Kurikulum Pendidikan Agama Islam Di Madrasah Tsanawiyah & Madrasah Aliyah Di SMK Lingua Prima Indralaya - Opi Shinta Cornelia; Dian Eka Wati; Ririn Dia Ayu Irma; Filza Ahlina; Lusiana Lusiana; Dwi Noviani (Jurnal Budi Pekerti Agama Islam, 2024)
The Merdeka Curriculum as an alternative curriculum overcomes learning setbacks which gives "Independent Learning" freedom to learning implementers, namely teachers and principals in compiling, implementing the learning process, and developing curriculum in schools paying attention to the needs and potentials of students. This research was conducted to provide an overview of the Merdeka Curriculum as a form of independent learning in elementary schools regarding the profile of Pancasila students, the structure of the Merdeka Curriculum in elementary schools, and the teaching tools used. The research was conducted using the Library Research method (literature study) and visited a website that presents information related to the Independent Learning Curriculum in elementary schools. In preparation for the implementation of the Merdeka Curriculum, teachers need to learn more about the Merdeka Curriculum and consider projects according to student phases in order to achieve meaningful, profound, and fun learning outcomes as well as students.